Pemanfaatan Lahan Pekarangan Di Kelurahan Kleak Kecamatan Malalayang Kota Manado - Tamboto, Christiani C. Putri; Manginsela , Elsje Pauline; Maweikere, Audrey J. Maria (Sam Ratulangi University, 2023)
This study aims to determine and describe the use of yard land in terms of aspects of living dispensaries, beauty, living kitchens, social and economic in Kleak Village. The study will be conducted from June to July 2023. The determination of the sample in this study was by purposive method. The data used are primary data and secondary data. Primary data were collected through observation and interviews using questionnaires to families who owned yard land in their homes. The total number of respondents was 7 people. Secondary data was obtained from the Malalayang sub-district office related to the demographics of the Kleak sub-district area. Secondary data is also obtained from the internet through google scholar in the form of publications, journal articles and theses related to the topic of Yard Land Use in Kleak Village, Malalayang District, Manado City. The results showed that the use of the yard as a living dispensary to reduce the consumption of chemical drugs by using spices planted in the yard while for ornamental plants as decoration to add beauty to the yard of the house (not traded plants) just to fill free time and hobbies. Planting plants as a living kitchen to increase the need for kitchen spices for cooking purposes and reduce the cost of spending on kitchen materials, by planting plants in the yard of the house is used as part of social interaction in the surrounding environment and yard land can also produce plants that have economic value. *eprm*